The distributional impact of social spending in Peru - Anja Gaentzsch (Freie Universität Berlin, School of Business & Economics, 2018)
Peru has made great progress in reducing poverty and inequality in the past decade alongside high economic growth. Albeit this progress, the incidence of poverty and inequality remain high. This paper examines the distributional and poverty impact of the public tax and transfer system in Peru. It applies an extended income approach that accounts for the value of publicly-provided health, education and childcare services. Accounting for public services is important since unequal access to basic services is a main development challenge for low and middle income countries. We find that public social spending reduces overall inequality by almost 7 Gini points. This reduction is mainly driven by in-kind benefits while the impact of taxation and direct cash transfers is small. Income differentials within regions explain approximately four fifths of overall inequality compared to diffierences between regions, which explain about one fifth. This ratio remains largely unaffected by public redistribution. Mean levels of welfare vary widely across regions. This is also because social spending achieves litte poverty reduction. It decreases absolute poverty by 2-3 percentage points in terms of monetary income and up to 9 percentage points or 25% when accounting for public service use. The largest share of the poor, over 50%, are not reached by social assistance. To tackle poverty more effectively, transfer levels and coverage need to be increased. Current policies seem insuffcient to achieve a more equitable income distribution.
Keywords: D31; I30; H53; I38; 330; income distribution; poverty; social protection; public services; non-cash income; Peru